THE ASIA PACIFIC MANAGEMENT AND BUSINESS APPLICATION: Looking Deeper Toward Management Research and Business Practices in the Growing Economics Regions - Irawanto, Dodi Wirawan (Department of Management, Faculty of Economics and Business, Brawijaya University, 2012)
EDITORIAL The Asia Pacific Management and Business Application: Looking Deeper Toward Management Research and Business Practices in the Growing Economics Regions.